Digital Transformation in Georgian Banking: Trends and Current Level of Adoption - Abuselidze, George; Zoidze, Tamriko (European Journal of Sustainable Development, 2024)
The significance of digital technologies is crucial in contemporary times. This is especially pertinent for the banking industry, enabling it to deliver high-quality customer service and address market challenges promptly. This article examines the current state of the Georgian banking system, focusing on digital services and products, and the advances banks have made in integrating innovative digital technologies. Using specific criteria, the study evaluates the level of digitization within the banking sector, identifying strengths and areas for improvement. The research also explores the digital transformation experiences of developed countries' banking sectors and considers how these could be implemented in Georgia, taking into account the unique context and challenges faced by the country. The study aims to assess the digital readiness and challenges faced by Georgia's banking sector, leading to the formulation of recommendations to speed up the digital transformation process and enhance competitiveness. Both quantitative and qualitative research methods are used in the research. The digital banking products and services offered by commercial banks are analyzed, with statistical conclusions derived from quantitative data, providing a comprehensive overview of the sector's digital maturity. In the end, the study evaluates the challenges and future prospects for the digital transformation of Georgia's banking system, offering strategic insights and practical solutions for policymakers and industry stakeholders. Keywords: Georgian banking, innovation, digital transformation, mobile banking, online banking, digital payments